2019
DOI: 10.1002/lsm.23156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsed 810 nm Al‐Ga‐As Diode Laser on Wound Healing Under Immunosuppression: A Molecular Insight

Abstract: Background and Objectives Dysregulated inflammation is one of the major contributing factors for the prevalence of non‐healing chronic wound in immunosuppressed subjects. Photobiomodulation (PBM) has emerged as a potential non‐thermal, light‐based therapeutic healing intervention for the treatment of impaired wounds. Study Design/Materials and Methods The present study delineates the underlying molecular mechanisms of PBM 810 nm laser‐induced full‐thickness cutaneous wound repair in immunosuppressed rats at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 57 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Based on this feature, we hypothesized that the explanation may lie in the indirect photothermal effect produced by CO 2 laser treatment. In addition, previous studies have revealed that high‐energy laser may exert a biostimulating effect on tissues while producing a photothermal effect, which may have a positive impact on wound healing [21–25]. This effect is unique to laser treatment, which distinguishes it from all other mechanical debridement methods.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this feature, we hypothesized that the explanation may lie in the indirect photothermal effect produced by CO 2 laser treatment. In addition, previous studies have revealed that high‐energy laser may exert a biostimulating effect on tissues while producing a photothermal effect, which may have a positive impact on wound healing [21–25]. This effect is unique to laser treatment, which distinguishes it from all other mechanical debridement methods.…”
Section: Discussionmentioning
confidence: 99%
“…El Khoury reported ( 33 ) that tPBM, by MRI, inhibited the default network, and Figueiro Longo et al ( 31 ) and associates treated patients with traumatic brain injury and found in serial DTI studies that the active group but not sham had marked improvements at 3-months in their fiber pathways, through re-myelinization. Recent work suggests that a membrane opsin, TRPV1 ( 47 ) and extracellular TGF-beta1 ( 48 ) appear to be involved in the anti-inflammatory effects of photobiomodulation.…”
Section: Introductionmentioning
confidence: 99%